Prospek Pengembangan Modal Usaha Petani Kecil Melalui Program P4K di Kabupaten Bantul - Nanik Dara Senjawati; Budi Widayanto (Jurnal Dinamika Sosial Ekonomi, 2000)
The study is aimed to investigate the development of the small farmers' capital in Small Farmer Development Program. The trend analysis was estimated by Ordinary Least Square methods. The results show that the credit under the program could not hasten the growth of own capital. That was indicated by the decrease in the own capital when the credit was suspended. The alternative methods in increasing the farmers' capital might be proposed as: (1). give disparities of the sum of credit depend on the kind business, (2). Increase the group savings, (3), implement the profit sharing business for the beginner groups.Key words: Small farmer, capital, empowering.